Penanaman kejujuran dalam membentuk karakter anak sejak usia dini melalui kantin kejujuran - Edy Suyanto (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
This paper aims to describe how to shape character and foster early childhood morals through the honesty canteen. The results of the discussion showed that the application of honesty canteen can instill an attitude of honesty in children, because children are the next generation of the nation that must be educated in a balanced manner between the knowledge and morals of children. The application of honesty canteen can also be instilled with an anticorruption attitude, and will also form a self-foundation in children when they grow up with a habit of being honest. Honesty canteen is an effort to educate children to behave honestly because honesty is an essential human nature. Where if honesty is given space and is in a good environment, it will develop by itself, so that the formation of children's character can be achieved in accordance with the expectations of parents and society.